Smoking and cessation treatment among persons with and without HIV in a U.S. integrated health system. (1st August 2020) - Lam, Jennifer O.; Levine-Hall, Tory; Hood, Nicole; Alexeeff, Stacey E.; Horberg, Michael A.; Young-Wolff, Kelly C.; Sterling, Stacy A.; Williams, Andrew; Weisner, Constance; Satre, Derek D.; Silverberg, Michael J.
Highlights: Smoking prevalence among persons with HIV (PWH) is decreasing, mirroring trends observed in persons without HIV. Given equal access to care, PWH are more likely to initiate cessation treatment than persons without HIV. Better integration of smoking cessation into HIV primary care is needed. Abstract: Background: Persons with HIV (PWH) are more likely to smoke and are more susceptible to the harmful effects of smoking than persons without HIV. We examined smoking patterns and use of cessation treatment among PWH and persons without HIV in a U.S. integrated health system. Methods: We identified adults (≥18 years) with HIV and demographically-matched persons without HIV between July 2013 and December 2017. Smoking status and cessation treatment were ascertained from health records. We calculated age-standardized annual prevalence of smoking and evaluated trends using Cochran-Armitage tests and Poisson regression. Factors associated with cessation treatment during the study period, and smoking in the last year of the study, were evaluated by HIV status using multivariable Poisson models. Results: The study included 11, 235 PWH and 227, 320 persons without HIV. Smoking prevalence was higher among PWH across all years but declined for both groups (from 16.6% to 14.6% in PWH and 11.6% to 10.5% in persons without HIV). Among smokers, PWH were more likely to initiate cessation treatment compared to persons without HIV (17.9% vs. 13.3%, covariate-adjusted prevalence ratio of 1.31, 95% CI = 1.15–1.50), with few differences in cessation treatment across subgroups of PWH. In 2017, smoking prevalence remained higher in PWH, especially among those who were younger or who had diagnoses of depression or substance use disorder. Conclusion: In a setting with access to cessation resources, smoking prevalence decreased both in PWH and persons without HIV. PWH had greater uptake of cessation treatment, which is encouraging for smoking reduction and improved health.